Average thermodynamic and spectral properties of plasma in and around dipolarizing flux bundles. Issue 6 (4th June 2015) - Runov, A.; Angelopoulos, V.; Gabrielse, C.; Liu, J.; Turner, D. L.; Zhou, X.‐Z.
Abstract Recent observations have suggested that spatially localized flows of high‐temperature, low‐density plasma carrying a dipolarized magnetic field (dipolarizing flux bundles, DFBs) play a key role in hot plasma transport toward the inner magnetosphere. What controls plasma heating in DFBs and how do thermodynamic parameters (such as density, temperature, pressure, and specific entropy) and spectral properties of the DFB population depend on ambient plasma sheet properties and geocentric distance R remains unknown. By statistical analysis of 271 DFB events detected by the Time History of Events and Macroscale Interactions during Substorms mission during the 2008–2009 tail seasons, we find that on average, plasma inside DFBs is a factor of 0.6 less dense and a factor of 1.5 to 2 hotter than ambient tail plasma. The radial profiles of average thermodynamic parameters inside and outside DFBs are similar; when fitted by the κ‐function, their energy spectra have similar κ‐exponents, but a factor of 2 larger peak energies inside DFBs. Our analysis suggests that average DFB plasma properties are closely linked to those of the ambient plasma sheet population. Estimations show that on average, adiabatic heating of the ambient plasma in the increased magnetic field is the major factor in DFB plasma heating.